Tanggung Jawab Dan Komitmen Pegawai Terhadap Produktivitas Kerja Di Biro Pemerintahan Umum Gubernur Sumatera Utara - Rafi Faizin; Azhari Akmal Tarigan (Moneter : Jurnal Ekonomi dan Keuangan, 2023)
This study aims to investigate how responsibility and commitment can affect employee performance. This study's research technique uses qualitative methods, or more specifically, observation techniques used over the course of a month in the North Sumatra Governor's office. The study's findings indicate that responsibility and dedication play a big part in employee performance since they affect job productivity inside the organization, which in turn affects how the public perceives the organization. Therefore, it can be claimed that the organization's function may help each employee become more committed and responsible. which will eventually be able to offer the public the greatest service.